Brain imaging patterns by magnetic resonance imaging in pediatric population using automatic segmentation by VolBrain - Silvério, M. (2022)
The interpretation of the pediatric brain is challenging due to the fact that its development is a dynamic process that continuously and rapidly changes at the macro- and microstructural levels, especially in the first 2 years of life. Another issue that makes interpretation difficult is the small size of brain structures and the limited experience of radiologists with the pattern and variability of maturation's activity. Consequently, there is some difficulty in distinguishing what is normal from what is pathological. Magnetic resonance allows the characterization of normal brain development, specially myelination patterns, which are important for understanding the maturation processes that occur after birth. It also enables the assessment of abnormalities that may occur throughout development. In addition to the rapid evolution of the pediatric brain that makes the assessment of structures by MRI and the interpretation of standard images and variants of normality difficult, there is an absence of standardized quantitative data needed to characterize the signal throughout the maturation of the normal brain. Thus, there remains a lack of information and the need to develop studies directed at children of lower age ranges. It is, therefore, particularly important to investigate and determine a normal standard for each developmental stage, in order to aid the process of comparability in the diagnosis of pathologies. In this sense, the following question was posed: "How do brain structures vary in fixed age groups in the pediatric population, as assessed by MRI?" The objectives of this article are: 1) to characterize brain structures at different stages of development using pediatric MRI; 2) to apply image processing algorithms in three-dimensional reconstruction to maximize the advantages of this method of study.